External signs of internal representations: developments in processing utterances and beliefs - Parsons, Sarah (2000)
Three factors in Referential Communication are worthy of special consideration: the utterance, the speaker's internal representation, and reality. These relationships form the 'referential triangle' of communication. This thesis explores how children and adults evaluate utterances when all three elements of the referential triangle need to be considered. The main aim was to investigate why utterances might be more difficult to understand than other externalisations of internal representations, such as pictorial representations of belief.